Managing the Integration of Spiritual Values for Character Formation: A Multi-Site Case Study in Indonesian Elementary Schools - Rahmi Rahmi; Fitriyani Kosasih (MASI Mandiri Edukasi, 2026)
This study examines how spiritual values are systematically integrated to strengthen students’ character formation through school management processes in elementary education. Employing a qualitative multi-site case study design, the research was conducted at SDN Nanggala 1 and SDN Ciranjang 1 in Cianjur Regency, Indonesia. Data were collected through in-depth interviews, participant observations, and document analysis, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that effective character development is strongly influenced by managerial and leadership practices rather than by religious instruction alone. Strategic planning, collaborative organization, consistent habituation through daily spiritual and social activities, and continuous behavioral evaluation enabled values such as discipline, responsibility, empathy, and respect to be embedded into everyday school life. Despite challenges related to limited time, varying teacher readiness, and difficulties in assessing character outcomes, adaptive leadership and stakeholder collaboration supported program sustainability. The study concludes that spirituality-based character education is most effective when managed as a structured and school-wide process. This research contributes to educational management literature by positioning spiritual value integration as a strategic mechanism for fostering sustainable character development in elementary schools.